Essays in economics of education and development - Cardim, Joana Azevedo e Castro de Almeida (2022)
Essays in Development Economics Although education is considered essential to economic development, it is still not accessible to everyone. This dissertation explores ways in which quality education can reach vulnerable people. The first chapter shows that the provision of a technology program to schools’ benefits students, namely through reducing teacher absenteeism. The second chapter shows that students from communities that present higher levels of cooperation have better grades. The third chapter looks at the effects of free childcare and finds that attending day-care makes girls more averse to disadvantageous inequality. The last chapter presents preliminary results on the trends and geography of education mobility in Europe.